The Tendency of Social Isolation in International Class Students of the Guidance and Counseling Department - Arfinda, Muhammad; Ifdil, Ifdil (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
Humans have a close dependence on patterns of social relations, so that they can influence their mindset and life, but in the international class majoring in Guidance and Counseling there are several symptoms of a tendency to social isolation, so this study aims to describe the tendency of social isolation that occurs in students of the Department Guidance and counseling. The method used in this research is descriptive quantitative. The results of this study show that the tendency of social isolation for international class students is in the moderate category with a percentage of 88.16%. which can be concluded that the average international class student has a tendency to social isolation, a lifestyle that tends to be individual and allows for other psychological disorders